2017
DOI: 10.1093/jmcb/mjx045
|View full text |Cite
|
Sign up to set email alerts
|

Mitosis-specific acetylation tunes Ran effector binding for chromosome segregation

Abstract: Stable transmission of genetic information during cell division requires faithful mitotic spindle assembly and chromosome segregation. The Ran GTPase plays a key role in mitotic spindle assembly. However, how the generation of a chemical gradient of Ran-GTP at the spindle is coupled to mitotic post-translational modifications has never been characterized. Here, we solved the complex structure of Ran with the nucleotide release factor Mog1 and delineated a novel mitosis-specific acetylation-regulated Ran–Mog1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…5, A-C). To identify the underlying cause, we analyzed the affected amino acid residues against the 3D structure of MOG1 as reported by Bao et al (15). As shown in Fig.…”
Section: Point Mutation Analysis Identifies Critical Amino Acids Of Mmentioning
confidence: 99%
See 3 more Smart Citations
“…5, A-C). To identify the underlying cause, we analyzed the affected amino acid residues against the 3D structure of MOG1 as reported by Bao et al (15). As shown in Fig.…”
Section: Point Mutation Analysis Identifies Critical Amino Acids Of Mmentioning
confidence: 99%
“…MOG1 has an interesting structure with a backbone formed by six-stranded antiparallel ␤-sheets flanked on both sides by helices (14). The solution structure of human MOG1 was determined recently by conventional NMR spectroscopy and has a sandwich-like structure with nine ␤-strands and four helices (15). The ␤3 to ␤9 form the central antiparallel ␤-sheets, which were packed by helices ␣2 and ␣4 on either side (15).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Acetyltransferase TIP60 has been well-studied in ATM activation, p53 activation, PML stabilization for DNA damage response, and genomic stability control (24 -28). Recently, our study revealed the function of TIP60 in chro-mosome stability control during mitosis through acetylating Aurora B (29) and RAN GTPase (30,31). However, the precise mechanisms underlying accurate kinetochore microtubule attachment remain obscure.…”
mentioning
confidence: 98%